Long-Term Remission Achieved by Ponatinib and Donor Lymphocytes Infusion in a Ph+ Acute Lymphoblastic Leukemia Patient in Molecular Relapse After Allogenic Stem Cell Transplant and Dasatinib: A Case Report - Botta, Cirino; Caruso, Nadia; Bossio, Sabrina; Storino, Francesca; Console, Giuseppe; Martino, Massimo; Mendicino, Francesco; Lucia, Eugenio; Morelli, Rosellina; Correale, Pierpaolo; Morabito, Fortunato; Gentile, Massimo; et al. (Frontiers in Oncology, 2020)
Currently, the prognosis of Ph+ acute lymphoblastic leukemia (Ph+ ALL) patients relapsing after an allogenic hematopoietic stem cell transplantation (allo-SCT) remains poor, with few therapeutic options available. Here we present the case of a 32 years old patient with dasatinib-resistant post-transplant molecular relapse of ALL, who received, as second-line therapy, the combination of ponatinib and donor lymphocyte infusion (DLI). The therapy was safe and the patient achieved a sustained minimal residual disease negative disease, still ongoing after 22 months, which was accompanied by several changes in the immune populations distribution within the bone marrow (i.e., the increase in the CD8/CD4 lymphocytes ratio). Our report provides evidence of the efficacy of the third generation TKI inhibitor ponatinib in combination with DLI as second line therapy for Ph+ ALL relapsing after an allo-SCT.